Vibration-Induced Kinesthetic Illusions and Corticospinal Excitability Changes. Issue 3 (4th May 2017) - Mancheva, Kapka; Rollnik, Jens D.; Wolf, Werner; Dengler, Reinhard; Kossev, Andon
ABSTRACT: The authors' aim was to investigate the changes of corticospinal excitability during kinesthetic illusions induced by tendon vibration. Motor-evoked potentials in response to transcranial magnetic stimulation were recorded from the vibrated flexor carpi radialis and its antagonist, extensor carpi radialis. The illusions were evoked under vision conditions without feedback for the position of the wrist (open or closed eyes). In these two conditions motor-evoked potential changes during vibration in the antagonist were not identical. This discrepancy may be a result of 2 simultaneously acting, different and opposite influences and the balance between them depends on visual conditions. Thus, the illusion was accompanied by the facilitation of corticospinal excitability in both vibrated muscle and its antagonist.